A Critical Analysis of Amina Wadud’s Feminist Hermeneutics in Qur’anic Interpretation - Ibrahim Hasan Ray (Modern Islamic Studies and Sharia Research, 2025)
This study examines Amina Wadud's feminist hermeneutics method in reading the Qur'an, focusing on her efforts to interpret the text with an awareness of the social context and experiences of women as subjects of interpretation. The research gap that this study aims to fill is the lack of studies in Indonesia that systematically analyze the methodological framework and ethical foundations of tawhid in Wadud's feminist hermeneutics, as most previous studies have been descriptive in nature and have not critically linked the methodological, ethical, and implicative dimensions of feminist readings of the Quran. This article positions itself to go beyond a general presentation of Wadud's thinking by offering a conceptual analysis that highlights how Wadud "stands at the edge of the text," integrates the principle of tawhid as the foundation of gender justice, and unravels the challenges and resistance faced by this approach in contemporary interpretive discourse. The research approach uses qualitative methods through library research with conceptual analysis of relevant literature. The results show that Wadud reconstructs inclusive and gender-just interpretation through dialogue between text and context, affirming tawhid as the basis for rejecting discrimination, while criticizing dominant patriarchal interpretations. In conclusion, these results are in line with the research objective of emphasizing the importance of tawhid-based feminist hermeneutics as an ethical-methodological foundation for gender-just interpretation of the Quran and opening up space for more empirical follow-up research.